2019
DOI: 10.1002/ange.201911720
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Bioinspired Carbohydrate Polymer with Mucoadhesive Properties

Abstract: Mucoadhesive polymers are of significant interest to the pharmaceutical, medical device, and cosmetic industries. Polysaccharides possessing charged functional groups, such as chitosan, are known for mucoadhesive properties but suffer from poor chemical definition and solubility, while the chemical synthesis of polysaccharides is challenging with few reported examples of synthetic carbohydrate polymers with engineered‐in ionic functionality. We report the design, synthesis, and evaluation of a synthetic, catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…127 The guar oligomer is retained by the hydrogel until it reaches the colonic environment when it is degraded by bacteria-secreted enzymes. The diffusion of guar oligomer inside the hydrogel was quantified by FRAP, which revealed that diffusion was greatly reduced compared with noninteracting 99 x Sustr et al 86,100 x Pinte et al 101 x Bruggen et al 102,103 x Nauman et al 104 x Prakash et al 105 x Balijepalli et al 106 x Jin-lei et al 107 x Grosskopf et al 16 x Govindaraj and Pos 4 x Hager et al 108 x Saito et al 109,110 x Sancataldo and Vetri 111 x Kvist et al 112 x Kindt et al 97 x Bui et al 113 x Kingsley al. 114 x Dey et al 115 x Devkota et al 116 x Waharte et al 117 x Sato et al 118 x Hashimoto et al 119 x probes and stayed constant over a couple of hours, resulting in a slow release.…”
Section: Homogenous Systemsmentioning
confidence: 99%
“…127 The guar oligomer is retained by the hydrogel until it reaches the colonic environment when it is degraded by bacteria-secreted enzymes. The diffusion of guar oligomer inside the hydrogel was quantified by FRAP, which revealed that diffusion was greatly reduced compared with noninteracting 99 x Sustr et al 86,100 x Pinte et al 101 x Bruggen et al 102,103 x Nauman et al 104 x Prakash et al 105 x Balijepalli et al 106 x Jin-lei et al 107 x Grosskopf et al 16 x Govindaraj and Pos 4 x Hager et al 108 x Saito et al 109,110 x Sancataldo and Vetri 111 x Kvist et al 112 x Kindt et al 97 x Bui et al 113 x Kingsley al. 114 x Dey et al 115 x Devkota et al 116 x Waharte et al 117 x Sato et al 118 x Hashimoto et al 119 x probes and stayed constant over a couple of hours, resulting in a slow release.…”
Section: Homogenous Systemsmentioning
confidence: 99%